Large shareholder diversification, corporate risk taking, and the benefits of changing to differential voting rights - Bauguess, Scott W.; Slovin, Myron B.; Sushka, Marie E. (Journal of Banking & Finance, 2012)
We show how the change to differential voting rights allows dominant shareholders to retain control even after selling substantial economic ownership in the firm and diversifying their wealth. This unbundling of cash flow and control rights leads to more dispersed economic ownership and a closer alignment of dominant and dispersed shareholder interests. When insiders sell sizeable amounts of their economic interests, firms increase capital expenditures, strengthen corporate focus, divest non-core operations, and generate superior industry-adjusted performance. The change to differential voting rights both fosters corporate control activity and creates higher takeover premiums that are paid equally to all shareholders.